2001
DOI: 10.1093/humrep/16.7.1382
|View full text |Cite
|
Sign up to set email alerts
|

Effects of female and male smoking on success rates of IVF and gamete intra-Fallopian transfer

Abstract: There is compelling evidence that couples should be made aware that smoking years before undergoing IVF and GIFT can impact treatment outcome. This study may also provide insight into the timing and effects of male and female smoking on natural reproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
1
13

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(76 citation statements)
references
References 24 publications
3
59
1
13
Order By: Relevance
“…However, the lower peak E2 levels [21,22] and recruitment of fewer follicles and oocytes [7,13,15,21,23,24] in smokers that were reported in earlier studies were not observed in our population, in which milder and less vigorous stimulation was required.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…However, the lower peak E2 levels [21,22] and recruitment of fewer follicles and oocytes [7,13,15,21,23,24] in smokers that were reported in earlier studies were not observed in our population, in which milder and less vigorous stimulation was required.…”
Section: Discussioncontrasting
confidence: 79%
“…Several meta-analyses and reviews have investigated the effect of smoking in patients undergoing IVF treatment [5][6][7]. They all found that compared to nonsmokers, smokers required a higher mean gonadotropin doses for ovarian stimulation, and had lower peak E2 levels, fewer oocytes retrieved, lower fertilization and implantation rates, and lower pregnancy and live-birth rates.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis of 2,314 first IVF cycles from eight studies showed that odds of pregnancy were almost halved by smoking [48]. In another study, couples (one or both) who ever smoked had an adjusted relative rate, RR, of 2.41 of not achieving an IVF pregnancy and 3.76 of not achieving a live birth [49]. Moreover, couples smoking more than 5 years had a RR of 4.27 of not achieving a pregnancy.…”
Section: Risks Associated With the Culture Of Gametes And Embryosmentioning
confidence: 99%
“…Additionally, various physical, occupational, behavioural and socio-economic factors affecting human fertility in men and women may also influence success of the IVF treatment [8][9][10][11][12][13]. Obesity and smoking are thought to be some of the most critical among these factors [4][5][6][7][8][9][10][11][12][13][14][15][16]. It has also been established that some drugs, heavy metals and solvents, may affect fertility [17][18][19].…”
Section: Introductionmentioning
confidence: 99%